Compensation strategies in speaking activities for non-English department students: poor and competent speakers - Syafryadin, Syafryadin; Martina, Feny; Salniwati, Salniwati (Universitas Muhammadiyah Sidoarjo, 2020)
This study investigated the compensation strategies which were used by competent and poor speakers to avoid communication gap in speaking activities. This study used descriptive quantitative desaign. The use of descriptive method because of this study was not searching about compararison or making prediction, but only finding out about mostly strategies used either competent or poor speakers in developing their speaking activities to avoid communication gap. Descriptive research is also chosen because it explores and catches social situation particularly in the class wholisticly, widely and deeply. Data collection used an observation sheet and a questionnaire. Population of this study was 83 students categorized as competent and poor speakers of semester 4 at English Study Program in one of the universities in Kendari. The findings of this study showed that the strategy which dominant used by either competent speakers or poor speakers as their group tendencies that was selecting the topic with the same overall average score of 4.0; competent speakers mostly used selecting the topic with the overall average of 4.0, adjusting or approximating the message with the overall average of 3.6 and using mime or gesture with the overall average of 3.5; poor speakers also mostly used selecting the topic with the overall average of 4.0 and coining word of 3.5. Competent speakers much more used compensation strategies than poor speakers. Thus, its major implication for pedagogy is that compensation strategies are extremely useful as guidance to avoid communication gap in speaking activities